Vitamin D supplementation in swines: Literature review (Research, Society and Development, 2023)
Vitamin D and its prohormones have become the focus of increasing research in recent years, revealing functions beyond calcium metabolism and bone formation. This includes interactions with the immune system, given the widespread expression of the vitamin D receptor in various body tissues such as the brain, heart, skin, intestine, gonads, prostate, breasts, and immune cells, in addition to bones, kidneys, and parathyroids. Recommended values vary across different information sources, largely dependent on the conditions under which they were established (experimental, commercial, or field-based). However, it is the nutritionist's role to adapt these values to specific production conditions and goals. Thus, this literature review aims to clarify the mechanism of metabolism, acquisition, and contribute to the controversy surrounding Vitamin D deficiency and Hypervitaminosis in pigs from the weaning of piglets to the finishing phase.